2022
DOI: 10.18388/abp.2020_5722
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin and morin reduces insulin resistance and endometrial hyperplasia in the rat model of polycystic ovarian syndrome through enhancement of inflammation and autophagic apoptosis

Abstract: Polycystic Ovary Syndrome (PCOS) is a gynecologic disorder with unsatisfactory treatment options. Hyperandrogenism and insulin resistance (IR) are two symptoms of PCOS. The majority of PCOS patients (approximately 50% to 70%) have IR and moderate diffuse inflammation of varying degrees. We investigated in-vitro and in-vivo effects of naringenin, morin and their combination on PCOS induced endometrial hyperplasia by interfering with the mTORC1 and mTORC2 signaling pathways. The vaginal smear test ensured the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The enhancement of ovarian histomorphological characteristics might be attributed to an anti-androgenic mechanism 54 of the silibinin as evident by the decrease in testosterone hormone level demonstrated in this study and the alleviation of endometrial hyperplasia might be attributed to the improved structural and functional microenvironment of the ovarian and uterine tissues. 55 , 56 The incomplete restoration of ovarian and uterine tissues in rats treated by silibinin alone is probably attributed to insufficient time-duration (19 days) of the treatment. Further investigations are needed to investigate the long-term treatment of silibinin with different doses and route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of ovarian histomorphological characteristics might be attributed to an anti-androgenic mechanism 54 of the silibinin as evident by the decrease in testosterone hormone level demonstrated in this study and the alleviation of endometrial hyperplasia might be attributed to the improved structural and functional microenvironment of the ovarian and uterine tissues. 55 , 56 The incomplete restoration of ovarian and uterine tissues in rats treated by silibinin alone is probably attributed to insufficient time-duration (19 days) of the treatment. Further investigations are needed to investigate the long-term treatment of silibinin with different doses and route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were seen, possibly due to the low duration of naringenin treatment and without any other combination, Daine-35, as used earlier (Wu, Yang, Han, et al 2022). However, naringenin treatment did not show normalization of the estrous cycle within the given duration of treatment as reported in the earlier studies (Hong et al, 2019;Yang et al, 2022). Add-on therapy of naringenin with metformin has been F I G U R E 1 1 Analysis of Estrous cycle/ovarian cycle analysis, body and organ weights, and oral glucose tolerance test in response to combined therapy of naringenin and metformin.…”
Section: Discussionmentioning
confidence: 64%
“…The dose of naringenin has been used earlier as 20 mg/kg body weight (b.wt.) for the determination of gut microbiota (Wu, Yang, Han, et al 2022), steroidogenic enzymes and antioxidants (Hong et al, 2019), and endometrial hyperplasia in the PCOS ovary (Yang et al, 2022). Further, in our research based on 4‐hydroxyisolucine (4‐HIL) PCOS management, we found 4‐HIL MED 50 mg/kg body weight in a similar PCOS model system (Indian patent reference no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Yang et al disclosed that naringin combined with morin could inhibit the proliferation of human endometrial adenocarcinoma cells. In their study, naringin inhibited PCOS-induced endometrial hyperplasia and regulated autophagy by blocking the mammalian target of rapamycin complex 1 (mTORC1)/mammalian target of rapamycin complex 2 (mTORC2) signaling, and morin increased the levels of Caspase-3 and LC3-phosphatidylethanolamine conjugate (LC3-II) ( Yang et al, 2022 ). In addition, naringin could change the elevated serum insulin level and maintain the typical morphology of the ovary in rats with PCOS ( Wu et al, 2022 ).…”
Section: Flavonoidsmentioning
confidence: 99%